Importance of paravertebral muscle quality in the etiology of degenerative lumbar spinal stenosis - Kaya, İsmail (The European Research Journal, 2023)
Objectives: Degenerative lumbar spinal stenosis (DLSS) is the leading cause of pain, disability, and loss of independence in older adults. In this study, the relationship between DLSS and paravertebral muscle thickness and density was investigated using computed tomography (CT) and magnetic resonance imaging (MRI) methods. Thus, the importance of muscles has been examined to take precautions in the name of preventive medicine. Methods: This study was planned as a cross-sectional study. The patient group (n = 77) who had surgery for DLSS and the control group (n = 77) were examined. A total of 154 participants (55 females and 22 males in each group) were evaluated retrospectively in terms of cross-sectional area (CSA) and density in the psoas, erector spina and multifidus muscles. In both groups age, gender and body mass index values equalized. Measurements was averaged from the mid-lumbar 3 level from both sides and multi-points. Results: There was no significant difference between muscle thicknesses (p > 0.05). When evaluated in terms of muscle densities, a significant difference was found between the patient and the control group in terms of psoas muscle (p < 0.05). Likewise, there is the same relationship between erector spinae muscle density and multifidus muscle density (p < 0.05). Conclusions: Roughly no difference was found between the patient and control groups in terms of CSA of the psoas, erector spinae and multifidus muscles, but it was observed that the muscle density, especially in the multifidus, decreased significantly in the patients. Our results suggest that paravertebral muscle density assessment is an important criterion in disease prediction and can inform preventive treatment.